A newly developed carrier for the vitrification of prepubertal testicular tissue and its comparison with four different carriers - ÇETİNEL, ŞULE (My University, 2022)
Research question: The cryopreservation of prepubertal testicular tissue is important for children who are to undergo gonadotoxic treatment. There is ongoing debate around the optimal carrier for an inexpensive and rapid vitrification technique. How efficient would a novel, practical and sterilizable metal brush be when compared with previously used carriers? Design: The testicular tissues of prepubertal rats were vitrified using four different carriers and evaluated by light microscopy and transmission electron microscopy. Results: Nuclei were easily discriminated in the metal brush, aluminium foil and high-security straw groups, but there was decreased discrimination of structures in the metal wire group. Minimal cytoplasmic degeneration, vacuolization and mild reversible degenerative effects were seen in spermatogonial stem cells and Sertoli cells in the metal brush group. Mild to moderate structural changes were found in the aluminium foil group. Severe pyknosis of the nuclei, a high degree of swelling, expansion of the endoplasmic reticulum, and swelling and blurring of the mitochondria were seen in the metal wire and high-security straw groups. The cell viabilities in the metal brush, aluminium foil, metal wire and high-security straw groups were 91.6 +/- 3.85%, 83.0 +/- 4.06%, 76.0 +/- 3.16% and 68.6 +/- 4.93%, respectively. Conclusions: The metal brush is a promising new carrier for prepubertal testis vitrification.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Biochemistry; Surgery Medicine Sciences; Obstetrics and Gynecology; Life Sciences; Natural Sciences; KADIN HASTALIKLARI & DOĞUM; Klinik Tıp; Klinik Tıp (MED); ÜREME BİYOLOJİSİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); OBSTETRICS & GYNECOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); REPRODUCTIVE BIOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); Doğum ve Jinekoloji; Biyokimya (tıbbi); Biochemistry (medical); Cryopreservation; Fertility preservation; Prepubertal testicular tissue; Spermatogonial stem cells; Vitrification; HUMAN OVARIAN TISSUE; FERTILITY PRESERVATION; CRYOPRESERVATION; TRANSPLANTATION; FOLLICLES; PROTOCOLS; CHILDREN; CANCER; CELLS; Cryopreservation; Fertility preservation; Prepubertal testicular tissue; Spermatogonial stem cells; Vitrification